PENGARUH KEPEMIMPINAN, MOTIVASI DAN PROFESIONALISME TERHADAP KINERJA KARYAWAN PT INDUSTRI KERETA API (PERSERO) DI MADIUN - Sutarno, Eny Kusumawardhani, Amin Wahyudi & (Universitas Slamet Riyadi, 2018)
This research aims to analyze the influence of leadership, motivationand professionalism of employees on performance of railway Industry PT(Persero) in Madiun. This study used a survey method, the type of data thedata used was qualitative and quantitative data, the source data used theprimary data and secondary data. The population in this research is theemployees of the railway Industry PT (Persero) in Madiun i.e. as many as848 employees. The number of samples in this research as much as 85employees, with sampling techniques using a purposive sampling. Methodsof data collection were used: questionnaire. Technique of data analysis usedthe test of validity, reliability test, test the assumptions of classical, andmultiple linear regression analysis, t-test, F-test and coefficient ofdetermination. The research results obtained the conclusion there is asignificant influence of leadership on performance of employees. There aresignificant effects of motivation on performance of employees. There is asignificant influence on performance of professionalism of employees.Keywords: leadership, motivation, professionalism, performance ofemployee